COVID-19 Lockdown 2020 Changed Patterns of Alcohol and Cannabis Use in Swiss Elite Athletes and Bodybuilders: Results From an Online Survey - Christian Imboden; Malte Christian Claussen; Malte Christian Claussen; Malte Christian Claussen; Samuel Iff; Boris B. Quednow; Boris B. Quednow; Erich Seifritz; Jörg Spörri; Jörg Spörri; Johannes Scherr; Johannes Scherr; et al. (Frontiers Media S.A., 2021)
Objectives: During the COVID-19 pandemic, increased patterns of substance use have been reported in the general population. However, whether this also applies to athletes is not yet clear. This study aimed to detect changes in alcohol consumption and cannabis use in elite athletes and bodybuilders during the first COVID-19 lockdown in Switzerland.Methods: Between April 25 and May 25, 2020, a cross-sectional online survey was conducted among bodybuilders and Swiss elite athletes who were active in Olympic sports and disciplines approved by the International Olympic Committee (IOC) on at least the national level. The collected data included information on alcohol and cannabis use during the last month (lockdown) and in the year before COVID-19 lockdown (pre-lockdown), daily training times, existential fears on a scale from 1 to 100, Patient Health Questionnaire-9 for depression (PHQ-9), Insomnia Severity Index (ISI), and State-Trait Anxiety Inventory (STAI).Results:N = 275 athletes (elite athletes: n = 193; bodybuilders: n = 82) was included in this study. Both pre-lockdown and during lockdown, more bodybuilders used cannabis (both time points: p < 0.001) than elite athletes, and more elite athletes drank alcohol (pre-lockdown: p = 0.005, lockdown: p = 0.002) compared to bodybuilders. During lockdown, fewer athletes drank alcohol compared to before, but those who continued drinking did so on more days per week (p < 0.001, Eta2 = 0.13). Elite athletes were more likely to increase their drinking with 17.7 vs. 8.2% in bodybuilders. When compared to pre-lockdown measures, the number of athletes using cannabis did not change during lockdown. Only three of 203 elite athletes reported using cannabis during lockdown; this contrasts with 16 of 85 bodybuilders. In a multivariate regression model, existential fears and a lower ISI score were significant predictors for increased alcohol consumption during the lockdown in the entire sample. In a model based on elite athletes only, male sex and a lower ISI score predicted increased alcohol consumption. In a bodybuilder-based model, predictors of increased alcohol consumption were existential fears and trait anxiety.Conclusion: We suggest identifying athletes who are at risk for increased alcohol and cannabis use; we suggest this to be able to professionally support them during stressful times, such as the COVID-19 pandemic.